2008
DOI: 10.1111/j.1479-8298.2008.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Lepidoptera captured on the East China Sea in 2005 and predicted migration sources

Abstract: This paper provides a list of moths captured in a region at latitudes 29-32°N and longitudes 127-130°E on the East China Sea on 14-28 June and 1-7 July 2005. Sixteen species of moths from the families Plutellidae, Crambidae, Sphingidae and Noctuidae were identified. Among these, three species were recorded on the East China Sea for the first time. The migration paths of the captured moths were analyzed using a threedimensional backward trajectory analysis method. Predicted migration sources for these moths are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The rice leaffolder, Cnaphalocrocis medinalis Guenée (Lepidoptera: Pyralidae), is a serious migratory insect pest causing significant damage to rice crops in many Asian countries (Kawazu et al , ). To control this pest species, application of synthetic insecticides have been used frequently for decades.…”
Section: Introductionmentioning
confidence: 99%
“…The rice leaffolder, Cnaphalocrocis medinalis Guenée (Lepidoptera: Pyralidae), is a serious migratory insect pest causing significant damage to rice crops in many Asian countries (Kawazu et al , ). To control this pest species, application of synthetic insecticides have been used frequently for decades.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we used the Oriental armyworm ( Mythimna separata Walker) as the host species. Mythimna separata naturally feeds on grasses but is also a destructive pest on corn and rice crops, particularly in Asia (Kawazu et al , 2008) and is considered one of the most important hosts of these three endoparasitoids.…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures are known to enhance the growth of CCW, and rainfall decreases the larval density because young larvae are vulnerable to water. Common cutworm cannot overwinter in Japan, and Kawazu et al (2008) predicted that CCW migrated to Japan from Fujian and Guangdong provinces in China and from Taiwan. Migration times and numbers of CCW differ from year to year because of yearly differences in wind direction and strength.…”
Section: Discussionmentioning
confidence: 99%
“…In Kyushu, Japan, CCW have been observed in almost all soybean fields. The adult moths arrive from areas outside Japan (Kawazu et al, 2008) and oviposit on leaves of soybean and other hosts; indeed, CCW has been reported to feed on the leaves of more than 120 plant species (Venette et al, 2003). The hatched larvae feed on the leaves day and night until pupation.…”
mentioning
confidence: 99%